Real‐world efficacy and safety of 12‐week sofosbuvir/velpatasvir treatment for patients with decompensated liver cirrhosis caused by hepatitis C virus infection. Issue 1 (20th October 2020) - Takaoka, Yoshinari; Miura, Kouichi; Morimoto, Naoki; Ikegami, Tadashi; Kakizaki, Satoru; Sato, Ken; Ueno, Takashi; Naganuma, Atsushi; Kosone, Takashi; Arai, Hirotaka; Hatanaka, Takeshi; Tahara, Toshiyuki; et al.
Abstract : Aim: This study aimed to evaluate the real‐world efficacy and safety of 12‐week sofosbuvir/velpatasvir (SOF/VEL) treatment for patients with decompensated liver cirrhosis caused by hepatitis C virus (HCV) infection. Methods: A total 72 of patients with Child–Pugh (CP) class B or C were enrolled. We evaluated the sustained virologic response at 12 weeks after the end of treatment (SVR12), adverse events (AEs), and changes in the liver function. Results: All participants had genotype 1 or 2 HCV infection. At baseline, the numbers of patients with CP class B and C were 59 and 13, respectively. The overall SVR12 rate was 95.8% (69/72); 94.9% (56/59) in CP class B and 100% (13/13) in CP class C. The serum albumin level, prothrombin time and ascites were significantly improved ( P  < 0.01); however, the serum bilirubin level and encephalopathy did not improve. Among patients who achieved SVR12, 75.0% showed an improvement in their CP score, while 5.9% showed a worsening. The presence of large portosystemic shunt (diameter ≥6 mm) and hyperbilirubinemia (≥2.0 mg/dL) were independent factors that interfered with the improvement in the CP score ( P  < 0.05). The most common AEs were encephalopathy (15.3%) and skin symptoms (7.9%). Two patients discontinued SOF/VEL due to AEs. Conclusions: Treatment with SOF/VEL for 12 weeks was relatively safe and effective for patients with decompensated cirrhosis. An SVR provided an improvement of the liver function in the majority of patients. However, large portosystemic shunt and hyperbilirubinemia were independent factors that interfered with the improvement in the CP score.